(untitled) (Ameghiniana, 2014)
"Two new species belonging to the trilobite family Calymenidae are described. Neseureius (Neseuretus) lipanensis n. sp. and Colpocoryphe perforata n. sp. come from the Acoite Formation (Lower-Middle Arenigian) that crops out in the westem flank ofthe Cordillera Oriental, Jujuy Province. Neseuretus and Colpocoryphe are described for the first time in the Acoite Formation; the later has not been previously reported from Argentina. Furthermore, Neseuretus ""kobayashi"" Harrington and Leanza frorn the Santa Gertrudis Formation, Gallinato creek, Salta Province is here revised and additional morphological information is provided."